ANALISIS PENERAPAN PAJAK PERTAMBAHAN NILAI PADA PT. NENGGAPRATAMA INTERNUSANTARA - Daud, Andromedha; Sabijono, Harijanto; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Tax is one of the very potential and quite dominant revenue because it has the function of budget and regulations. Taxation in which there is a VAT element is also part of the government's fiscal policy because one type of tax imposed by the government is Value Added Tax (VAT). The purpose of this study is to determine the application of Value Added Tax conducted by PT. Nenggapratama Internusantara. Based on the results of the research, the Application of Value Added Tax PT. Nenggapratama Internusantara is in conformity with Law no. 42 of 2009. The accounting treatment of Value Added Tax by PT. Nenggapratama Internusantara as a taxable entrepreneur is in accordance with Law no. 42 of 2009 which is 10% for domestic delivery.Keywords: Â Value Added Tax (VAT), Input Tax, Output Tax